Organic phase transmetallation approach for synthesis of hollow Ni-Au nanocomposites with tunable cavity size - Sardar, Debasmita; Ahmed, Md Azaharuddin; Bandyopadhyay, Sudipta; Ghosalya, Manoj Kumar; Bala, Tanushree (New Journal Of Chemistry, 2018)
Ni-Au nanocomposites in the form of hollow spheres with controlled cavity size have been successfully synthesized by the transmetallation reaction between hydrophobized Ni nanoparticles and hydrophobized Au precursors. This can be considered as a fairly unique synthesis strategy that does not require any additional external reductants. The synthesis is carried out in a nonpolar solvent and precise tuning of the cavity size has been achieved only by varying the ratio of the two reacting components. A detailed characterization has been performed via UV-vis spectroscopy, XPS, TEM, EDAX, and SEM. The mechanistic aspect is established from FTIR. SQUID-VSM confirmed the magnificent superparamagnetism of the nanocomposites.

Oxidative disproportionation of MoS2/GO to MoS2/MoO3-x/RGO : integrated and plasmonic 2D-multifunctional nanocomposites for solar hydrogen generation from near-infrared and visible regions - Patra, Kshirodra Kumar; Ghosalya, Manoj Kumar; Bajpai, Himanshu; Raj, Sreeya; Gopinath, Chinnakonda S. (Journal of Physical Chemistry C, 2019)
Two dimensional (2D) semiconductor materials have been recently demonstrated to be effective plasmonic materials and alternatives to costly noble metals. However, tuning the plasmon resonance of 2D semiconductors and integrating with another material or semiconductor for various applications, such as solar light harvesting, remains a challenge. Herein, we designed a simple and attractive method, which facilitates the diffusion of oxygen from the graphene oxide (GO) layers of the MoS2/GO (MG) composite to oxidize the MoS2 layers significantly due to thermal treatment under inert atmosphere. This is the key step in the formation of MoS2/MoO3-x/RGO (MMR) (x = 0, 0.5, and 1, and all stoichiometries co-exist), due to disproportionation of MoS2/GO, with bulk heterojunctions among the components. The observed behavior is attributed to the oxidation of Mo4+ cations (of MoS2) to higher oxidation states in MMR (Mo(5+ )and Mo6+ of MoO3-x), which also alters the valence-band electronic structure and work function of the resulting composite. The 2D MoO3-x layers with a large amount of Mo5+ oxidation states enables facile charge carrier generation due to plasmonic effect, whereas MoS2 provides active sites for catalysis. The solar H-2 generation was demonstrated in the visible and near-infrared region by combining both the plasmonic and catalytic effects in one composite. These results demonstrate the important role of RGO to provide energy-level alignment, charge carrier diffusion, and help to generate plasmonic effect in the composite.